How Different Diets Affect Gastrointestinal System Microbiota? - Muhammet Ali CEBİRBAY (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology)
Numerous billions of microbial species inhabit the human gut, generating a dynamic environment that influences health and illness. Following the PRISMA guidelines, a database search included studies published up to 2010-2024. We identified 132 studies that met the inclusion criteria. Diet has an important role in regulating gastrointestinal system (GIS) microbiota features. Dietary long- or short-term changes and nutrient intake are related to varyingGIS microbiota species. High-protein diets provide short chain fatty acids with amino acid transformation linked with balancing the Firmicutes/Bacteroidetes ratio. In contrast, high-carbohydrate diets, except oligosaccharide intake, have a subversive activity on GIS microbiota. Mediterranean and vegan diets sustain better GIS microbiota variety because of their high indigestible fiber contents. The widespread view that a gluten-free diet promotes Celiac Disease has controversial findings besides GIS microbiota. Intermittent fasting affects microbial diversity with digestion, biochemical signal, and pathways depending upon changing time restrictions and meal size portions. This study summarizes the current understanding of the changes in microbial composition, metabolic effects, and disease related to positive and negative healthy risks and beneficial roles related positive and negative healthy risks and beneficial roles. It influences the dynamics of the GIS microbiota, such as dysbiosis.